Pulmonary herniation 3 years after video-assisted thoracic surgery lobectomy - Ankur Gupta; Christian Hulett; Jonathan West (CSIRO Publishing, 2021)
ABSTRACT Pulmonary herniation is defined as protrusion of lung parenchyma through thoracic wall weakness. We present a case of a 69-year-old male who presented to a rural hospital with a 4-day history of cough, right-sided chest pain and exertional shortness of breath. His past medical history included right lung adenocarcinoma treated with right upper lobe lobectomy via video-assisted thorascopic surgery (VATS) 3 years prior. Chest inspection revealed decreased chest wall movements on the right side with no visible chest bulge and on palpation non-tender chest bilaterally with palpable crepitus of the right anterior chest. Chest expansion was reduced on the right side associated with hyper-resonant percussion. Auscultation revealed diffuse bilateral rhonchi. A CT of the chest showed herniation of the right lung through a post-operative defect in the thoracic wall. The patient was initiated on codeine linctus for cough suppression and remained haemodynamically stable for his 3-day admission. He remained asymptomatic at his 4-week follow up with complete resolution of surgical emphysema. We could find no other case reports of VATS lobectomy where lung herniation presented years after surgery.